2013
DOI: 10.1542/peds.2012-1371
|View full text |Cite
|
Sign up to set email alerts
|

Facial Dysmorphism Across the Fetal Alcohol Spectrum

Abstract: Heat maps and morphing visualizations of face signatures may help clinicians detect facial dysmorphism across the fetal alcohol spectrum. Face signature graphs show potential for identifying nonsyndromal heavily exposed children who lack the classic facial phenotype but have cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(139 citation statements)
references
References 42 publications
6
131
1
1
Order By: Relevance
“…Of particular note, ND-PAE criteria failed to reliably identify the presence of partial FAS and FAS, which diagnoses incorporate cardinal facial features that are highly specific to the effects of prenatal alcohol exposure. 20 Although the impairment cut-off for ND-PAE may be conservative in this study, the low sensitivity of the DSM-5 criteria is in part rooted in its organizational structure. The DSM-5 criteria as is imply a shared neurobehavioral profile among patients affected by ND-PAE.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Of particular note, ND-PAE criteria failed to reliably identify the presence of partial FAS and FAS, which diagnoses incorporate cardinal facial features that are highly specific to the effects of prenatal alcohol exposure. 20 Although the impairment cut-off for ND-PAE may be conservative in this study, the low sensitivity of the DSM-5 criteria is in part rooted in its organizational structure. The DSM-5 criteria as is imply a shared neurobehavioral profile among patients affected by ND-PAE.…”
Section: Discussionmentioning
confidence: 88%
“…20 These facial characteristics include short palpebral fissures, smooth philtrum and thin upper lip, and were measured in consort with the Canadian guidelines 8 and the 4-digit code. 7 Given the specificity of these facial features to prenatal alcohol effects, classification of ND-PAE should be correlated to FAS and partial FAS.…”
mentioning
confidence: 99%
“…Facial dysmorphology was characterized by dense surface modeling of 3-dimensional images (21). Principal components (PCs) were derived by reducing 28,000 data points using a mathematical representation resulting in 10 facial, 10 philtral, and 10 profile PCs.…”
Section: Association Analysis In the Collaborative Initiative On Fetamentioning
confidence: 99%
“…2, 46 Borenstein et al 47 reported that using 3D volumes of the fetal head in order to define the relative position of the maxilla and mandible in fetuses with trisomy 18 compared to chromosomally normal individuals improves the detection rate to 92%. Although fetal alcohol syndrome refers to facial dysmorphisms, 48 research has not reported variations in fetal facial movements. Given the changes in the facial anatomy, there is the potential to establish not only the dysmorphism by analyzing the fetal facial anatomy but also variations in movements.…”
Section: Use Of Ultrasound Images Can We Use Fetal Facial Movements Fmentioning
confidence: 99%